What Is It Like to Make a Prototype? Practitioner Reflections on the Intersection of User Experience and Digital Humanities/Social Sciences during the Design and Delivery of the “Getting to Mount Resilience” Prototype - Ashlin Lee (Informatics, 2023)
The digital humanities and social sciences are critical for addressing societal challenges such as climate change and disaster risk reduction. One way in which the digital humanities and social sciences add value, particularly in an increasingly digitised society, is by engaging different communities through digital services and products. Alongside this observation, the field of user experience (UX) has also become popular in industrial settings. UX specifically concerns designing and developing digital products and solutions, and, while it is popular in business and other academic domains, there is disquiet in the digital humanities/social sciences towards UX and a general lack of engagement. This paper shares the reflections and insights of a digital humanities/social science practitioner working on a UX project to build a prototype demonstrator for disaster risk reduction. Insights come from formal developmental and participatory evaluation activities, as well as qualitative self-reflection. The paper identifies lessons learnt, noting challenges experienced—including feelings of uncertainty and platform dependency—and reflects on the hesitancy practitioners may have and potential barriers in participation between UX and the digital humanities/social science. It concludes that digital humanities/social science practitioners have few skill barriers and offer a valued perspective, but unclear opportunities for critical engagement may present a barrier.